Investigations about porosity analyzing of AAC. Issue 4 (1st September 2018) - Anders, Nicole
Abstract: Autoclaved aerated concrete (AAC) as a building material is characterized by its very good thermal insulation. This is achieved by a very high porosity of the microstructure. The size of the pores ranges from millimeters to nanometers and depends on the position as well as on the origin of the pore. It can be distinguished in propellant pores, web pores, and intercrystalline or interparticle pores. Because of the broad pore size range it is not fully understood until now, which pore sizes significantly and to what extent affect the building material qualities. The AAC's entire pore size distribution can only be detected by the combination of different microstructure analysis methods. For this purpose the nitrogen sorption analysis, mercury intrusion, and 3‐D microcomputer tomography was used as an effective combination. AAC samples that show different mineralogical phase compositions because of the differentiation of the formulation, were tested. On the basis of these samples and the pore size distribution, which is usually used for the description of the frost and frost‐deicing salt resistance of concrete, initial insights into the influence of the respective pore size on building material properties of the AAC could be gained.